Pengaruh Kredit Bermasalah (NPL) dan Likuiditas (LDR) Terhadap Tingkat Profitabilitas (ROA) pada PT Bank Rakyat Indonesia Agroniaga Tbk Tahun 2010-2019 - I Ketut Darma; Ajeng Kristina Ningsih; I Nyoman Senimantara (Warmadewa Economic Development Journal (WEDJ), 2021)
This study was conducted to analyze the effect of Non-Performing Loans (NPL) and Liquidity (LDR) on Profitability (ROA). Time Series data is used in this study and tested using quantitative analysis techniques. Multiple linear regression test, classical assumption test, t test and F test are the techniques used in data analysis. The results of the t test show that the NPL Non-Performing Loans variable has a significant negative effect on Profitability, and the LDR Liquidity variable has an insignificant negative effect on lending.